2021
DOI: 10.1002/app.50866
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of natural fibers based green rubber composites: Properties, current status, and future perspectives

Abstract: The searching of suitable alternatives to petroleum‐based fillers is an uncompromising challenge in present day rubber research. Recently, natural fibers are the part of great attention of both academic and industrial researchers due to their easy availability, environmental friendliness, and biodegradability. Natural fiber is cellulose‐rich material, which is preferentially used as alternative filler in rubber technology. This article reviews current advances in natural fibers filled rubber composites in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 100 publications
(157 reference statements)
0
26
0
Order By: Relevance
“…Hardness is a characteristic of reinforced polymeric materials that depends on the cohesion of the fibers and their structure, presenting greater difficulty to be penetrated by other bodies. The investigations of Roy et al [4] and Wahab et al [89] reported a directly proportional relationship with the density of the material. Significant increases in the hardness of reinforced polymers occur with high percentages of natural fibers present in the matrix [10].…”
Section: Properties Of Polymers Reinforced With Natural Fibersmentioning
confidence: 94%
See 3 more Smart Citations
“…Hardness is a characteristic of reinforced polymeric materials that depends on the cohesion of the fibers and their structure, presenting greater difficulty to be penetrated by other bodies. The investigations of Roy et al [4] and Wahab et al [89] reported a directly proportional relationship with the density of the material. Significant increases in the hardness of reinforced polymers occur with high percentages of natural fibers present in the matrix [10].…”
Section: Properties Of Polymers Reinforced With Natural Fibersmentioning
confidence: 94%
“…Silane is another coupling agent, responsible for improving mechanical properties to achieve thermal stability in the residual polymeric matrix. Silane molecules form covalent bonds through siloxane bridges, improving its interfacial adhesion; the effectiveness is due to the formation of Silanol (Si − OH) groups that form strong bonds with the hydroxyl groups − OH of the fibers [4,10,74].…”
Section: Chemical Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rubber composites have been investigated using renewable, nonpetroleum-based filler sources such as kenaf [1], chitosan [2], starch [3][4][5], soy proteins [6], and other fibre [7][8][9][10][11]. Even though some of these materials have shown potential reinforcing capabilities, the industry appears hesitant to experiment with filler materials that are fundamentally different from carbon black (CB) in terms of appearance and source.…”
Section: Introductionmentioning
confidence: 99%